Method for analytical describing of the bulk carrier loading operations and optimizing them according to the criterion of the nautical safety (Transport systems and technologies, 2020)
The nautical safety of bulk carriers is largely determined by their correct loading. Available ship instruments do not allow for prompt cargo operations planning and real time vessel state controlling during their realization. The vessel responsible officer has to spend considerable time preparing the plan for loading (unloading) the vessel. The plan, often already prepared and approved by the Captain, has to be changed rapidly due to the changed conditions of cargo operations at the port. The high intensity of cargo operations at modern bulk terminals and the lack of sufficient time to prepare and verify the new cargo plan may create a risk of cargo holds being overloaded. This may lead to deterioration in the local and longitudinal strength of the hull and a violation in the seaworthiness of the vessel. The solution to this problem should be the creation of new computer system that will automate the bulk carriers loading operations planning, as well as making possible rapid changes to prepared plan when it become necessary. Such system should be based on a method (strategy) for optimization the distribution of a certain quantity of bulk cargo, taking into account the availability of port facilities and the design of the vessel itself, her nautical parameters, stability, longitudinal and local strength. In order to achieve this objective, it is necessary to formalize the cargo operations in terms of the mathematical model of the vessel and to establish the functional relationship between the parameters affecting the seaworthiness of the vessel. Obviously, the development of this method is a promising area of scientific research aimed to improve the safety of bulk vessels.The article describes the method of formalization of the loading operations of a bulk vessel with the task of choosing the best strategy for carrying out cargo operations according to the criterion of continuous seaworthiness of the vessel.
Keywords: : bulk carrier, cargo operations, analytical description, loading (discharging) plan, nautical safety, cargo operations optimization